(untitled) (Academia Journal of Medicine, 2018)
Background: A retrospective cohort study to compare the pregnancy complications and foetal outcomes in pregnancies complicated by diabetes mellitus. Subjects and Methods: One hundred and eighty five diabetic pregnant patients who delivered at the Department of Obstetric & Gynecology, University of Nigeria, Nsukka. during the 3-year-period formed the subjects of this study. There were 27(14.6%) (type 1) - insulin dependent diabetics, group 1, 19 (10.2%)(type 2), non insulin dependent diabetic patients who constituted group 2 and 139(75.2 %) gestational diabetic patients who made up group 3. Data extracted from the case files included maternal age, gravidity, parity , number of abortions, gestational age at booking, time of diagnosis of diabetes mellitus, complications during pregnancy, birth weight, placental weight. Results: There were no statistically significant differences in the three groups regarding the mean gravidity, parity, birth weight and placental weight (p>0.05). However, statistically significant differences were found with respect to the mean maternal age, gestation at booking, fasting blood sugar, and gestation at delivery (p<0.05). Out of 139 gestational diabetics, 23(16.5 %) were diagnosed by the 14" week of pregnancy while 24(17.2 %) were diagnosed between the 15- 27 weeks of gestation. The control of blood sugar was adjudged to be poor in 32% of gestational diabetics, 50% of type 2 diabetics and 69 % of type I diabetics, with statistically significant difference between the groups, (p<0.05). Although there was statistically significant difference between the groups regarding one of the pregnancy compli- cations( polyhydramnios) (p<0.05), none were found in other complications (p>0.05). The overall caesarean section rate was 48%. The overall perinatal mortality was 5.7%, all the deaths occurred in babies born to patients with gestational diabetes. Conclusion: Gestational diabetes accounted for all the fetal losses in this study, while polyhydramnios was the most common antenatal complication which was significantly higher in type 1 diabetics.